(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article discusses the propaganda of ideology in the field of exploitation of the economy of the Soviet power in Uzbekistan, separate views of the political processes of the activity of the department of propaganda and agitation of the Soviet government in the development of exploitation in agriculture.